Levels and trends of adolescent girl's undernutrition and anemia in West and Central Africa from 1998 to 2017 - Le Dain, Anne-Sophie; Sagalova, Vera; Sodjinou, Roger; Tou, El Hassane; Ntambi, John; Vollmer, Sebastian; Zagre, Noel Marie (Journal of global health, 2021)
Background Adolescence is a highly vulnerable period of human life characterized by substantial physiological and cognitive changes for which adequate nutrition is crucial. To date, evidence on determinants, prevalence, and trends of undernutrition and anemia for the entire West and Central African region is missing. This paper provides evidence on trends and levels of adolescent anemia and undernutrition in West and Central Africa. Methods We pooled all Demographic and Health Surveys (DHS) for West and Central African countries that were conducted between 1986 and 2017 to analyze levels and trends of adolescent anemia and undernutrition. We investigated the association of adolescent undernutrition and anemia within this region with World Bank income level classification of the country. Results Our findings suggest that the regional prevalence of adolescent anemia and undernutrition remained high at 45% and 19% respectively over the last 20 years. Anemia increased in about one third of countries and undernutrition in about two thirds over the studied period. On the aggregated level, these trends are largely masked and both levels remained stable in the entire region between the years 1998 and 2017. Results of multivariable regression analysis indicate an association of adolescence with undernutrition and anemia, which was independent of socio-economic factors such as income, education, and place of residence. Conclusion We conclude that levels of adolescent undernutrition and anemia remain high with little progress over the last 20 years and that adolescence is a significant correlate of both anemia and undernutrition. Given the recognition of the international community that adolescent nutrition is an important public health concern in resource-poor settings, there is an urgent need to improve data availability, quality, and use for decision-making and to design successful high-impact interventions to combat adolescent malnutrition in low- and middle-income countries.
Gesehen am 16.11.2021